Alteration of the cleavage distance of Fok I restriction endonuclease by insertion mutagenesis. - Li, L (1993)
Fok I restriction endonuclease recognizes the nonpalindromic pentadeoxyribonucleotide 5'-GGATG-3'.5'-CATCC-3' in duplex DNA and cleaves 9 and 13 nucleotides away from the recognition site. Recently, we reported the presence of two distinct and separable protein domains within this enzyme--one for the sequence-specific recognition and the other for endonuclease activity. Here, we report the construction of two insertion mutants of Fok I endonuclease. The mutant enzymes were purified, and their cleavage properties were characterized. The mutants have the same DNA sequence specificity as the wild-type enzyme. However, compared with the wild-type enzyme, they cleave one nucleotide further away from the recognition site on both strands of the DNA substrates. Thus, it is possible to alter the cleavage distance of Fok I by protein engineering.